Interrelationship of Capitalisation, Market Power and Profitability in Selected Food and Beverages Firms in Nigeria - Adedeji, Elijah Adeyinka Adedeji Adeyinka (Advances in Social Sciences Research Journal, 2014)
This study evaluated the interrelationship of capitalisation, market power and profitability in Food and Beverages Firms in Nigeria. Specifically, the relationship between capitalisation and market power, profitability and market power, also capitalisation and profitability were assessed. Six companies were purposively selected from Food and Beverages Firms, three from the Food firms and three from the Beverages firms to meet the needs of this panel study. Data for the study were collected using secondary sources within the period of ten years (2001-2010). The interrelationships between capitalisation, market power and profitability were analysed using Pearson Product Moment Correlation Coefficient (PPMCC) and Panel Data Analysis (PDA). Findings indicated that there is a positive significant impact of capitalisation on profitability in food firms (r = 0.561, p = 0.015). Capitalisation has a positive significant effect on market power with (r = 0.678, p = 0.001) for food firms, and (r = 0.932, p = 0.001) for beverages firms respectively. In addition, a positive relationship was also found to exist between capitalisation size and corporate profitability as (r = 0.885, p = 0.000) for food firms, and (r = 0.643, p = 0.000) for beverages firms. Based on these findings, the study concluded that there exists a positive and significant interrelationship between capitalisation, market power and profitability of the sampled firms. The study therefore recommended that management must see to an increase in total asset and total equity that will lead to an increase in market share and providing positive return on equity for their firms.